Portraying the Russian-Ukrainian Conflict on the German Facebook Social Network - Bacys, Tomas (Žurnalistikos tyrimai, 2019)
The article reviews the concept of information war, the functioning of social media and their impact. The newest information war technologies are being used to form the image of the conflict between Russia and Ukraine in Facebook social network and German-speaking community. It examines the methods and objectives influencing and manipulating consumers. The article reveals how the conflict between Russia and Ukraine in Germany’s Facebook social space is represented. The analysis of Facebook pages resulted in an analysis of visual content abundantly found regarding the Russian-Ukrainian conflict.